VD_FINDINFO HC / 2022 / 97 vom 11. März 2022 - VD Tribunal cantonal (2022)
BAIL À LOYER, CONGÉ DE REPRÉSAILLES, REJET DE LA DEMANDE | 271 al. 1 CO, 271a al. 1 CO, 272 CO, 311 al. 1 CPC (CH), 317 al. 1 CPC (CH)